2023
DOI: 10.47602/johah.v3i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Belongingness, Social Connectedness, and Life Satisfaction in College Students after COVID-19 Pandemic

Abstract: University students' sense of belonging has been greatly underrated since the pandemic, despite the fact that school belonging has been studied for many years. Due to school closings during the pandemic, college students lost the majority of their social connections at their university, and they have trouble rebuilding their social networks after the pandemic. In the present study, the mediating role of social connectedness in the relationship between life satisfaction and university sense of belonging was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The emphasis in this study on teachers as key facilitators of students' school belonging is consistent with findings documented in the existing literature. Avcı (2023), whose research carries particular weight in supporting the findings of the present study and who deals with the area of university students' school belonging after COVID-19, emphasizes the central role of professors in this context. Avcı asserts that professors hold a crucial position in shaping students' sense of school belonging, and emphasizes the importance of establishing close and meaningful relationships with professors as a means of fostering high levels of school belonging.…”
Section: Story 6 By the Participant 13 Thsupporting
confidence: 75%
See 2 more Smart Citations
“…The emphasis in this study on teachers as key facilitators of students' school belonging is consistent with findings documented in the existing literature. Avcı (2023), whose research carries particular weight in supporting the findings of the present study and who deals with the area of university students' school belonging after COVID-19, emphasizes the central role of professors in this context. Avcı asserts that professors hold a crucial position in shaping students' sense of school belonging, and emphasizes the importance of establishing close and meaningful relationships with professors as a means of fostering high levels of school belonging.…”
Section: Story 6 By the Participant 13 Thsupporting
confidence: 75%
“…A comprehensive literature review was conducted to examine existing research on school belonging, university students' school belonging, school belonging during the COVID-19 pandemic, online interpretative phenomenological analysis (OIPA), and online photovoice (OPV). The review revealed that students at all levels, including university students, encountered challenges related to school belonging both before and after the onset of the COVID-19 pandemic (Ahn & Davis, 2020;Arslan, 2021;Avcı, 2023). Based on these findings, the researcher, who holds a professorship in the Department of Social Science Education, turned her attention to studying the school affiliation of social science students, recognizing the lack of studies that examined the school affiliation of this particular group of students.…”
Section: College Belonging Among University Students During Covid-19:...mentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic caused negative effects on the physical (Liu et al, 2020), and psychosocial health and well-being of children and adolescents (Arslan et al, 2022;Avcı, 2023;Gifford-Smith & Brownell, 2003;Majercakova Albertova & Bolekova, 2022;Panda et al, 2021;Ravens-Sieberer et al, 2021;Xie et al, 2020;Zhou et al, 2020b). Many international studies confirm the burden of children and adolescents, throughout the COVID-19 pandemic, with anxiety, depression and post-traumatic stress (Kar & Bastia 2006;Ma et al, 2021;Stavridou et al, 2020;Yıldırım & Çiçek, 2022).…”
mentioning
confidence: 99%
“…Studies on students' sense of belonging at school have shown a positive relationship with life satisfaction (Arslan et al, 2020;Avcı, 2023), subjective well-being , psychological well-being (Arslan & Allen, 2016;Arslan & Coşkun, 2023), and a negative relationship with internalized and externalized problem behavior and substance abuse (Arslan, 2022b;Arslan et al, 2020) and peer bullying at school (Xu & Fang, 2021). On the other hand, a study by Parr et al (2020) found that school belonging was positively related to belonging in general and negatively related to depression.…”
mentioning
confidence: 99%